Effect of Vitamin C, Vitamin E and superoxide Dismutase Mimetic tempol on Dexamethasone Induced Experimental Weight Loss In wistar rats. - Biradar, Karnakumar V (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTDexamethasone is widely used Immunosuppressant and Anti-inflammatory agent. Its use is associated with evolution of Insulin Resistance and Hypertension and loss in body weight these are probably due to dyssregulation of physiology. So in the present study, effect of Antioxidant like Vitamin C (Ascorbic acid), Vitamin E (Î±-Tocopherol) and SOD Mimetic Tempol (2,2,6,6,-tetramethyl-4-hydroxy-1-piperidinyloxy) was administered in the dose of (100mg/kg /day, mixed in water and food pallets were soaked in it, 100mg/kg /day mixed in sesame oil and food pallets were soaked in it, and 1mmol/L in drinking water respectevily) and started from the initial day and continued throughout the study period for 14 days (Prophylactic regimen) and started from 8th day onwards the initiation of Dexamethasone and continued throughout the study period (Therapeutic regimen). Experimental Induced weight loss by using Dexamethasone (20Âµg/kg /once daily, subcutaneously) for 7 and 14 days in male Wister rats (240-300g) and estimated food intake, water intake, body weight daily and plasma total cholesterol at the last experiment day. From the finding of present study, Vitamin C, Vitamin E and SOD mimetic Tempol prevented /reversed the Dexamethasone induced decrease in body weight and prevent the decreased food intake only in preventive regimen. Vitamin E and vitamin C prevents decreased water intake in preventive and curative regimen respectively. There was no significant effect was observed in total cholesterol level in both the regimens.